2015
DOI: 10.1007/s13524-014-0362-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Mortality on Fertility: Population Dynamics After a Natural Disaster

Abstract: Understanding how mortality and fertility are linked is essential to the study of population dynamics. We investigate the fertility response to an unanticipated mortality shock that resulted from the 2004 Indian Ocean tsunami, which killed large shares of the residents of some Indonesian communities but caused no deaths in neighboring communities. Using population-representative multilevel longitudinal data, we identify a behavioral fertility response to mortality exposure, both at the level of a couple and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(116 citation statements)
references
References 55 publications
5
108
2
1
Order By: Relevance
“…Similar to the earthquake studies, this examination found elevated fertility rates in the disaster zone one to four years following the tsunami (Nobles et al, 2015). This study also found strong evidence to support the idea that the death of one’s child prompts a higher fertility response.…”
Section: Natural Disasters and Fertilitysupporting
confidence: 69%
See 2 more Smart Citations
“…Similar to the earthquake studies, this examination found elevated fertility rates in the disaster zone one to four years following the tsunami (Nobles et al, 2015). This study also found strong evidence to support the idea that the death of one’s child prompts a higher fertility response.…”
Section: Natural Disasters and Fertilitysupporting
confidence: 69%
“…This theory becomes more relevant in the event of family member deaths, particular one’s own children. Strong empirical evidence for replacement theory was found in a study of the 2004 Indian Ocean Tsunami and from post-earthquake fertility research in India, Pakistan and Turkey (Finlay, 2009; Nobles et al, 2015). …”
Section: Theoretical Approaches To Fertility Change In Response To Namentioning
confidence: 98%
See 1 more Smart Citation
“…Existing research on shocks and migration has typically examined large-scale shocks that affect a large population or geographic area, such as economic crisis (Curran, Meijer-Irons, and Garip 2016;Green and Winters 2010;Martin 2009) or natural disasters like Hurricane Katrina or the 2004 Indian Ocean tsunami (Fussell, Sastry, and VanLandingham 2010;Groen and Polivka 2010;Nobles, Frankenberg, and Thomas 2015). This research often focuses on differences in shock responses by socioeconomic status (e.g., Curran, Meijer-Irons, and Garip 2016;Green and Winters 2010;Martin 2009;Nobles, Frankenberg, and Thomas 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This research often focuses on differences in shock responses by socioeconomic status (e.g., Curran, Meijer-Irons, and Garip 2016;Green and Winters 2010;Martin 2009;Nobles, Frankenberg, and Thomas 2015). For instance, evidence from the Irish famine in the 1840s shows that those who had the financial means to emigrate to the United States and mainland Europe survived at remarkably higher rates than those who remained in Ireland (Ó Gráda and O'Rourke 1997).…”
Section: Introductionmentioning
confidence: 99%